Modelling financial wellbeing among young employees in Malaysia during Movement Control Order (MCO) / Nurul Labanihuda Abdull Rahman and Noor ‘Izzati Ahmad Shafiai - Abdull Rahman, Nurul Labanihuda; Ahmad Shafiai, Noor ‘Izzati (Universiti Teknologi MARA, Perlis, 2021)
Financial wellbeing is important for individuals to have a better life which is achievable by managing their finance. In fact, due to the Covid-19 pandemic, Malaysia has witnessed a loss of employment among young employees. Previous research relating to financial wellbeing has focused on the factors which are financial literacy and financial problems towards financial wellbeing. However, financial capability and work environment were not much explored. Therefore, this research will target young employees aged 20-40 who are affected during Movement Control Order (MCO) in the Northern Area. This paper presents the factors that will be examined and several issues on the inconsistent results from previous studies. The findings from this study are important to identify which determinant gives impact to the financial wellbeing and faced by young employees in Malaysia. Furthermore, employers will gain additional information regarding their employees' financial situation and able to overcome their difficulties. The government will also be able to provide financial assistance or job placement for young employees who are affected by this financial constraint in their life.